Extension Marketing: Building a Successful Local Extension Marketing Campaign: AEC396/WC077, rev. 12/2017 - Telg, Ricky; Irani, Tracy; Varvorines, James (EDIS, 2017)
This EDIS publication, focusing on the foundations of marketing communications, is the first of a five-part EDIS publications series on developing marketing campaigns for your local Cooperative Extension program. The Extension Marketing series includes publications on campaign planning and audience analysis development, integrated marketing, creative, social media and news media strategies, and budgets and evaluation. This 2-page fact sheet is a minor revision written by Ricky Telg, Tracy Irani, and James Varvorines, and published by the Department of Agricultural Education and Communication, December 2017. AEC396/WC077: Extension Marketing: Building a Successful Local Extension Marketing Campaign (ufl.edu)